Development of Artificial Intelligence-Based Animated Flashcards to Enhance Understanding of Earth's Surface Change Concepts - Sri Cahyani; Rita Istiana; Suci Siti Lathifah (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Low conceptual understanding among students regarding earth surface changes in West Java's geographical context stemmed from limited learning media. Textbooks and two-dimensional images dominated the learning process, making it difficult for students to understand dynamic and abstract phenomena. This study aimed to develop AI-based Animated Flashcards and test their feasibility and effectiveness in improving students' conceptual understanding. The Research and Development (R&D) method was employed using the ADDIE model. The subjects consisted of 17 fifth-grade students. The research instruments included validation sheets for subject matter, language, and media experts, as well as a conceptual understanding test administered via pre-test and post-test. Validation results showed that the developed media achieved 98.5% from media experts, 98% from material experts, and 98% from language experts, categorizing it as highly feasible. The effectiveness test demonstrated an increase in the students' average score from 64.5 in the pretest to 88 in the posttest. The N-Gain analysis yielded a score of 76, falling into the high category. Thus, the AI-based Animated Flashcards on earth surface changes in West Java's geography were highly feasible and effective in enhancing student understanding.